AKTIVITAS ANTIBAKTERI KITOSAN TERHADAP BAKTERI S.aureus - Mardiyah Kurniasih; Dwi Kartika (Universitas Jenderal Soedirman, 2009)
Chitosan is the N-deacetylated derivative of chitin. Chitosan is biodegradable, biocompatible and non-toxic. Chitosan is polycationic in acidic media and give antibacterial activity. In this paper, antibacterial activity of chitosan have been studied.Chitosan had been isolated from white shrimp. Antibacterial activity of chitosan solutions was examined against S. aureus The result showed that antimicrobial effect on S. aureus was strengthened as the choitosan concentrate decreased.